The Influence of Service Quality and Customer Satisfaction on Customer Loyalty at Bank BPD Bali - PASUPATI, Bayu; LAKSMI, Putu Ayu Sita (PT Keberlanjutan Strategis Indonesia, 2025)
This study aims to analyze the influence of service quality and customer satisfaction on customer loyalty at Bank BPD Bali. This study uses a quantitative approach with a survey method by distributing questionnaires to 150 active customer respondents of Bank BPD Bali. The data analysis technique used is multiple linear regression with the help of the SPSS program version 25. The results of the study indicate that service quality has a positive and significant effect on customer loyalty, as well as customer satisfaction has a positive and significant effect on customer loyalty. In addition, the results of the F test indicate that service quality and customer satisfaction simultaneously have a significant effect on customer loyalty. The coefficient of determination (R²) value of 0.486 indicates that 48.6% of the variation in customer loyalty can be explained by service quality and customer satisfaction, while other factors outside the research model influence the rest. This finding emphasizes the importance of improving service quality and customer satisfaction as a primary strategy in building long-term customer loyalty at Bank BPD Bali.